2019
DOI: 10.1002/fut.22070
|View full text |Cite
|
Sign up to set email alerts
|

Informed options trading on the implied volatility surface: A cross‐sectional approach

Abstract: This study investigates the cross‐sectional implication of informed options trading across different strikes and maturities. We explore the term structure perspective of the one‐way information transmission from options markets to stock markets by adopting well‐known option‐implied volatility measures to examine stock return predictability. Using equity options data for U.S. listed stocks spanning 2000–2013, we find that the shape of the long‐term implied volatility curve exhibits extra predictive power for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…For markets with liquid long‐maturity options, researchers have also looked at both the pure term structure of volatility (the time dimension) as well as the volatility surface—the mapping of IV with respect to both strike and time to maturity. Some examples of such studies include Chalamandaris and Tsekrekos (2011), Guo et al (2014), Chalamandaris and Tsekrekos (2014), Guo et al (2018), Kearney et al (2019, and references therein), and Kim et al (2020). Since liquidity in stock options in India is restricted to those with short maturity, exploring the time dimension or the volatility surface is outside the scope of our study.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
See 3 more Smart Citations
“…For markets with liquid long‐maturity options, researchers have also looked at both the pure term structure of volatility (the time dimension) as well as the volatility surface—the mapping of IV with respect to both strike and time to maturity. Some examples of such studies include Chalamandaris and Tsekrekos (2011), Guo et al (2014), Chalamandaris and Tsekrekos (2014), Guo et al (2018), Kearney et al (2019, and references therein), and Kim et al (2020). Since liquidity in stock options in India is restricted to those with short maturity, exploring the time dimension or the volatility surface is outside the scope of our study.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…Alexander (2001) showed that similar to the term structure, the three principal components of volatility can also be understood in terms of the level, the slope, and the curvature of the volatility smile. In the literature on modeling volatility smile; however, the DNS model has only been predominantly used to model the volatility term structure, with examples including Chalamandaris and Tsekrekos (2011), Guo et al (2014), Chalamandaris and Tsekrekos (2014), Guo et al (2018), Kearney et al (2019, and references therein), and Kim et al (2020).…”
Section: Modeling Volatility Smile Using the Dns Approachmentioning
confidence: 99%
See 2 more Smart Citations